Efficiency of one-against-one game situations in the Polish soccer national team and their opponents during UEFA European Championship matches - Szwarc, A.; Kromke, K.; Duda, H.; Soroka, A.; Radziminski, L. (Baltic Journal of Health and Physical Activity, 2024)
Introduction: The purpose of this study was to assess the efficiency in one against one (1v1) game situations of Polish national team soccer players and their opponents in 12 matches of the group stage in 4 consecutive cup finals at the European Championship in the years 2008-2021.